LEGAL PROTECTION OF THE GUARANTOR ON THE MAKING OF ADDENDUM TO THE CREDIT AGREEMENT WITHOUT THE GUARANTOR'S CONSENT - Johan, Valencia Christabel; Sri Widyawati (Faculty of Law, Universitas Pekalongan, 2024)
The legal relationship between creditors and debtors is based on a credit agreement which can be made in the form of a private deed or notarial deed. A credit agreement is a basic agreement that can be supplemented with an accessory agreement in the form of a guarantee agreement, both material guarantees and individual guarantees. The changes to the credit agreement can be made in the form of an addendum to the credit agreement. Changes to credit agreements without involving the collateral provider can give rise to disputes, as happened in the case of Supreme Court decision Number 3464 K/Pdt/2019, where the Creditor and Debtor entered into a private addendum agreement to the working capital credit agreement without the consent of the third party providing collateral. Making an addendum agreement to a working capital credit agreement without approval and an authentic deed raises some questions. Based on this case, the problem that will be discussed in this research is about the validity of addendums to credit agreements without the guarantor's approval as well as preventive legal protection for parties in making credit and guarantee agreements. This research aims to analyze the validity of credit agreement addendums without guarantor approval and legal protection for making credit agreement addendums without guarantor approval. The research method is a doctrinal research method. Based on this, this paper discusses the legal protection of guarantors for making addendums to credit agreements without the guarantor's approval. The results of this research are that making Addendum 1 (first) and Addendum 2 (second) to the quo credit agreement without the guarantor's approval is a valid agreement and the role of the notary in making authentic deeds and legal counseling is a form of preventive protection in a quo case decisions